P2-S3.01 STI risk among persons attending burning man in 2010. (10th July 2011) - Marcus, J L; Bernstein, K T; Philip, S S
Abstract : Background: Burning Man is a week-long event held annually over Labour Day in the Nevada desert, with over 50 000 attendees in 2010. We aimed to assess the potential for STI transmission among San Francisco attendees and the availability and acceptability of safer-sex services at Burning Man. Methods: We conducted a survey among a convenience sample of persons who attended Burning Man in 2010. An online questionnaire on demographics, sexual practices, and safer-sex services at Burning Man was created on SurveyMonkey and advertised on two email lists, one for all attendees and one for those living in San Francisco. Attendees were invited to participate anonymously from 1 week through 6 weeks after the event. We conducted a descriptive analysis of the responses. Results: Of the 1477 persons who completed the survey during 10 September–22 October 2010, most were heterosexual men (45.1%), heterosexual women (30.0%), or men who have sex with men (12.4%); of white race/ethnicity (86.5%); and from 25 to 44 years of age (62.5%). The majority (70.6%) had attended the event in prior years, and 17.8% resided in San Francisco. Over one quarter (28.5%) had been previously diagnosed with an STI. Of the 69.8% who reported having oral, vaginal, or anal sex at Burning Man, almost half (43.5%) reported sex with new partners. Although most attendees (86.3%) noticed that condoms were available at the event, nearly one quarter (23.0%) of respondents with new partners had intercourse without a condom, of whom two thirds (64.9%) did not plan to test for STIs during the month after the event. Of those planning to test, 49.3% planned to test with a private doctor, 23.9% at a community clinic, and 19.7% at an STI clinic. Only 2.6% of attendees reported that STI testing was available at the event; 41.3% said they would use the service if it were available. Conclusions: Although some safer-sex services were available at Burning Man in 2010, attendees reported unprotected intercourse with new partners during the event, a behaviour that confers high risk for STI acquisition. Large gatherings such as Burning Man might present opportunities for rapid STI transmission among geographically diverse sexual networks. Local health jurisdictions, both in the host location and those in which event attendees reside, should consider further assessment of STI transmission and prevention at Burning Man and similar events.